2003
DOI: 10.1016/s1097-2765(03)00134-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of CREB Target Genes Reveals A Core Promoter Requirement for cAMP Responsiveness

Abstract: We have employed a hidden Markov model (HMM) based on known cAMP responsive elements to search for putative CREB target genes. The best scoring sites were positionally conserved between mouse and human orthologs, suggesting that this parameter can be used to enrich for true CREB targets. Target validation experiments revealed a core promoter requirement for transcriptional induction via CREB; TATA-less promoters were unresponsive to cAMP compared to TATA-containing genes, despite comparable binding of CREB to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(145 citation statements)
references
References 28 publications
6
137
1
1
Order By: Relevance
“…To compare gene expression levels of c-Myc target genes in HOX11 þ versus HOX11 À T-ALL cells (Zeller et al, 2003), we used a similar bioinformatics approach to compile two subgroups: set I consists of cMyc-inducible genes (22 probe sets) identified in c-Myc global chromatin immunoprecipitation experiments that contain promoter-associated E-boxes and set II consists of genes (35 probe sets) identified in c-Myc global chromatin immunoprecipitation experiments whose expression positively correlates with c-myc mRNA levels in multiple tissues and cell lines (correlation coefficient >0.69) (Li et al, 2003). As can be seen in Table 1 Among other genes expressed at significantly higher levels in Sil and K3P cells than in Jurkat cells were targets (17 probe sets) of the cAMP response elementbinding protein CREB (>2.8-fold, Po0.03; Table 1 and Supplementary Information file 'Filtered data.xls', CREB sheet) (Conkright et al, 2003) and a subset of genes (29 probe sets) involved in mitochondrial function (two-fold, Po0.001; Table 1 and Supplementary Information file 'Filtered data.xls', Mitochondrial sheet), the latter genes potential downstream targets of the c-Myc/NRF-1 and CREB transcriptional networks (Kelly and Scarpulla, 2004). In addition, significantly elevated expression (17-26-fold; P o 0.02 and 0.001, respectively, in K3P and Sil cells) was observed for a subset of genes (14 probe sets) induced by interferon (IFN) ( Table 1 and Supplementary Information file 'Filtered data.xls', IFN sheet) (Krasnoselskaya- Riz et al, 2002).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…To compare gene expression levels of c-Myc target genes in HOX11 þ versus HOX11 À T-ALL cells (Zeller et al, 2003), we used a similar bioinformatics approach to compile two subgroups: set I consists of cMyc-inducible genes (22 probe sets) identified in c-Myc global chromatin immunoprecipitation experiments that contain promoter-associated E-boxes and set II consists of genes (35 probe sets) identified in c-Myc global chromatin immunoprecipitation experiments whose expression positively correlates with c-myc mRNA levels in multiple tissues and cell lines (correlation coefficient >0.69) (Li et al, 2003). As can be seen in Table 1 Among other genes expressed at significantly higher levels in Sil and K3P cells than in Jurkat cells were targets (17 probe sets) of the cAMP response elementbinding protein CREB (>2.8-fold, Po0.03; Table 1 and Supplementary Information file 'Filtered data.xls', CREB sheet) (Conkright et al, 2003) and a subset of genes (29 probe sets) involved in mitochondrial function (two-fold, Po0.001; Table 1 and Supplementary Information file 'Filtered data.xls', Mitochondrial sheet), the latter genes potential downstream targets of the c-Myc/NRF-1 and CREB transcriptional networks (Kelly and Scarpulla, 2004). In addition, significantly elevated expression (17-26-fold; P o 0.02 and 0.001, respectively, in K3P and Sil cells) was observed for a subset of genes (14 probe sets) induced by interferon (IFN) ( Table 1 and Supplementary Information file 'Filtered data.xls', IFN sheet) (Krasnoselskaya- Riz et al, 2002).…”
Section: Resultsmentioning
confidence: 94%
“…P-values were calculated using the paired Student's t-test. a HOX11 signature genes were identified by Ferrando et al (2002); E2F target genes were characterized by Ren et al (2002) and Weinmann et al (2002); set I Myc target genes are c-Myc-inducible genes identified in c-Myc global chromatin immunoprecipitation experiments that contain promoter-associated E-boxes ; set II Myc 'target' genes were identified in c-Myc global chromatin immunoprecipitation experiments and their expression positively correlates with c-myc mRNA levels in multiple tissues and cell lines (correlation coefficient >0.69) (Li et al, 2003); CREB target genes were extracted from the study by Conkright et al (2003); the set of Wnt-related genes was compiled from this work; IFN-induced genes were selected from the study by Krasnoselskaya-Riz et al (2002); and mitochondrial genes were chosen from the current data. Gene lists described in the text are provided as Supplementary Information HOX11 and G 1 /S transcription I Riz and RG Hawley observed that HOX11 downregulated transcription from the intact HSV tk promoter, albeit at higher concentrations of input DNA .…”
Section: Validation Of Microarray Data and Hox11 Transcriptional Mechmentioning
confidence: 99%
“…Profile hidden Markov models (pHMMs) for full CRE and half CRE sites were built based on known CREB target genes and were used to search for positional conserved sites as described in ref. 13. The training set sequences and the pHMMs are available at http:͞͞ natural.salk.edu͞CREB.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293T and MIN6 cells, human islets, and primary hepatocytes were cultured, transfected with dominant negative A-CREB expression vector or infected with A-CREB adenovirus, and harvested for mRNA analyses (10,13,15). To identify fasting-inducible genes, liver RNAs were harvested from male C57BL͞6 mice after 18 h of fasting or 14 h of fasting followed by 4 h of refeeding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation